Analysis of some extreme temperature indices over Iraq - YASEEN K, AL-TIMIMI; ALAA M, AL-LAMI; HASANAIN K A, AL-SHAMARTI; SAMIR K. , AL-MAAMORY (MAUSAM, 2020)
Climate change has negative impacts on different sectors. Generally, data display significant changes in the properties of extreme events. Daily minimum and maximum temperatures data for 36 meteorological stations of Iraq (1981-2017) were analysed to detect the significant trend and the magnitude trend extreme temperature indices over the 36-year period. RClimDex was used to compute indices and simple regression method was used for trend analysis. The results show that all stations displayed a significant increase in the annual average of maximum value of maximum temperature TXx and the annual average of maximum value of minimum temperature TNx. For the annual diurnal temperature range, about 81.6% of stations have a decreasing trend, while 18.4% have an increasing trend. The TXn index shows 78.9 has a decreasing trend for all stations except 5.3% have no change and 15.8% have an increasing trend. In contrast, the represent of TNn index demonstrate a decreasing trend for 63.2% of stations and 31.6% have an increasing trend fall all stations. Analysis of temperature extremes revealed a significant increase in most stations, which also shows that the country has seen a trend of warming.